Error control in finite elements for fluid modelling. - Onomor, E. M. (Cranfield University, 1997)
The main objective of this thesis was to ascertain and to catalogue the possible sources of errors in the finite element method when used for fluid modelling. Some of these errors are inherent in the finite element method whilst others are introduced by the user when performing a fluid mechanical analysis. This thesis distinguishes from the two and provides where possible, ways of preventing or controlling them. The form is based on the SAFESA Technical manual, which is an equivalent for structural analyses. Focus is then made, as an example, on a real world problem; "The Backward Facing Step" where, based on experimental data an element sensitivity analysis is performed within ANSYS/FLOTRAN. This analysis attempts to determine the magnitude of errors associated with prescribed element distortions in relation to aspect ratio, skew angle and taper ratio. The results contained within are in the form of graphical velocity profile plots, contour plots and tables at the varying distortions. The results show a strong deviation from the control mesh as the distortion is increased.
Keywords: Finite element method; fluid modelling; fluid mechanical analysis; element distortion; aspect ratio; skew angle; taper ratio